Diffusion of radiogenic helium in natural uranium oxides - Roudil, Danièle; Bonhoure, Jessica; Pik, Raphaël; Cuney, Michel; Jégou, Christophe; Gauthier-Lafaye, F. (Journal of nuclear materials, 2008)
The issue of nuclear waste management – and especially spent fuel disposal – demands further research on the long-term behavior of helium and its impact on physical changes in UO 2 and (U,Pu)O 2 matrices subjected to self-irradiation. Helium produced by radioactive decay of the actinides concentrates in the grains or is trapped at the grain boundaries. Various scenarios can be considered, and can have a significant effect on the radionuclide source terms that will be accessible to water after the canisters have been breached. Helium production and matrix damage is generally simulated by external irradiation or with actinide-doped materials. A natural uranium oxide sample was studied to acquire data on the behavior of radiogenic helium and its diffusion under self-irradiation in spent fuel. The sample from the Pen Ar Ran deposit in the Vendée region of France dated at 320 ± 9 million of years was selected for its simple geological history, making it a suitable natural analog of spent fuel under repository conditions during the initial period in a closed system not subject to mass transfer with the surrounding environment. Helium outgassing measured by mass spectrometry to determine the He diffusion coefficients through the ore shows that: (i) a maximum of 5% (2.1% on average) of the helium produced during the last 320 Ma in this natural analog was conserved, (ii) about 33% of the residual helium is occluded in the matrix and vacancy defects (about 10 −5 mol g −1) and 67% in bubbles that were analyzed by HRTEM. A similar distribution has been observed in spent fuel and in (U 0.9,Pu 0.1)O 2. The results obtained for the natural Pen Ar Ran sample can be applied by analogy to spent fuel, especially in terms of the apparent solubility limit and the formation, characteristics and behavior of the helium bubbles.